Examining the Role of Digital Literacy in Enhancing Arabic Language Acquisition Among Non-Native Speakers: Challenges and Opportunities - Abdulwasiu Isiaq Nasirudeen; Khalid Chtaibi (CV. Samuel Manurung and Co, 2026)
Given the rapid integration of digital technologies in language education and the unique linguistic complexity of Arabic, urgent research is needed to empirically determine how learners’ digital literacy competencies influence Arabic as a Foreign Language acquisition. This mixed-methods study investigates the relationship between digital literacy levels and language proficiency among 124 non-native Arabic learners enrolled in university-level AFL programs. Quantitative data were collected using a validated digital literacy scale adapted from the European Digital Competence Framework (DigComp) and a standardized Arabic proficiency test aligned with ACTFL benchmarks. Qualitative interviews and classroom observations explored learner perceptions and instructional practices. Results revealed statistically significant correlations between digital literacy skills-particularly information navigation, multimodal communication, and content creation-and reading comprehension, writing accuracy, and listening proficiency. Findings indicate that digitally literate learners demonstrate greater autonomy, increased exposure to authentic media, and more effective utilization of learning tools. Key challenges include unequal access to technology, limited pedagogical integration of digital tools, and learner dependency on machine translation. The study underscores the necessity of embedding digital literacy instruction within AFL curricula and provides recommendations for teacher training, curricular design, and future research